Serum C-reactive protein levels in severe and very severe pneumonia in children - Ni Putu Sucita Wahyu Dewi; Putu Siadi Purniti; Roni Naning (Indonesian Pediatric Society, 2012)
Background Pneumonia is a major cause of death in children fromdeveloping countries. It is difficult to assess pneumonia severity ifclinical symptoms of pneumonia are unclear, co-morbidities occursimultaneously, or there is an absence of consolidation or infiltrateson chest radiograph. Examination of C-reactive protein (CRP)levels can help to determine the severity of pneumonia.Objective To compare serum CRP levels in severe and very severepneumonia cases.Methods This was a cross-sectional study on pediatric patientsaged> 28 days up to 60 months v.ith a diagnosis of severe or verysevere pneumonia. Subjects were hospitalized at the Departmentof Child Health, Udayana University Medical SchooliSanglahHospital, Denpasar from May 2010 to January 2011. There were30 subjects in each group, severe or very severe pneumonia. Datawere analyzed using Mann-Whitney and ANCOVA tests withstatistical significance set at P < 0.05.Results There were significant differences in median serum CRPlevels in the severe and very severe pneumonia groups. The verysevere pneumonia group had a median CRP level of 54.75 mgiL(lQrange 0.22 to 216.00) and the severe pneumonia group had amedian CRP level ofl6.06 mgiL (IQ range 0.97 to 89.35). SerumCRP levels were influenced by the severity of pneumonia (P =0.002) and the timing of the CRP examination (P = 0.001).Conclusion Subjects with very severe pneumonia hadsignificantly higher median CRP level compared to that of subjectswith severe pneumonia. [Paediatr Indones. 2012;52:161A].